The Philosophy of Existentialism: Individual Awareness in Indonesian Education: Filsafat Existentialisme: Kesadaran Individu dalam Pendidikan Indonesia - Purnama, Aditya Yoga; Putri, Agnesi Sekarsari; Saputri, Ragil (Politeknik Harapan Bangsa Surakarta, 2021)
The philosophy of existentialism emerged driven by the uncertain world conditions due to world wars. So existentialism is present as a thought movement that emphasizes human subjectivity and freedom. This study has a purpose for reflection. Reflection means the process of understanding events in the mind or experience that is owned. This study uses descriptive qualitative research. This study utilizes a literature search. The literature search process begins with key phrases such as â€œexistentialismâ€, â€œeducationâ€ and â€œawarenessâ€. Man must exist, which means realizing that he exists to control himself and act on his behalf. The philosophy of existentialism talks about human existence, while talking about humans means questioning educational issues. Each person is unique, which is different from one another. Realizing this is important for students, parents, teachers, principals, board members, and all those involved in education. Education is expected to realize the